Influencing Community Involvement in School: A school community council - Preston, Jane (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
The purpose of this qualitative research was to explore the role a School Community Council (SCC) played in encouraging community involvement in a kindergarten to grade 12 school. Via 35 interviews, thematic data reflected that the SCC’s influence was limited. As analyzed through social capital theory, SCC members shared thin levels of trust, which influenced the association’s impact on community involvement. Research implications underscore the need for policymakers to reconsider SCC membership timelines.